Potential social risk factors for teenage pregnancy in Sarawak - Panting, Albeny Joslyn; Abdullah, Haslinda; Roslan, Samsilah; Ismail, Ismi Arif (Universiti Putra Malaysia Press, 2019)
Teenage pregnancy is among the main social issues that involves Sarawak teenagers. Teenage pregnancy may lead to various social, psychological, and physiological effects to the mother and child. Sarawak is one of the states in Malaysia that recorded a substantial number of teenage pregnancy cases. As such, an in-depth understanding of this issue may provide some important inputs for evidence-based sexual and reproductive health prevention programs. Therefore, the aim of this review is to identify the potential underlying social risk factors that might be contributed to teenage pregnancy cases in Sarawak. The literature review had identified at least six social risk factors that might contribute to teenage pregnancy cases in Sarawak. Those social risk factors were rural–urban migration, dysfunctional family relationship, flaws in marriage customary law, alcohol and drug abuse, low awareness on sexual and reproductive health, and pornography. A better understanding of this issue can strengthen the effectiveness of health education strategies toward improving sexual and reproductive health among the Sarawak’s young population.